2012
DOI: 10.1007/s12253-012-9525-9
|View full text |Cite
|
Sign up to set email alerts
|

Microvessel Density and Status of p53 Protein as Potential Prognostic Factors for Adjuvant Anthracycline Chemotherapy in Retrospective Analysis of Early Breast Cancer Patients Group

Abstract: A considerable subgroup of patients with early breast cancer does not address benefits of anthracycline based chemotherapy. The aim of this retrospective study was to investigate the effect of microvessel density (MVD) and status of p53 protein on 5-year disease free survival (DFS) in the group of breast cancer patients treated with anthracyclines in adjuvant setting. Correlations between MVD, p53 status and other clinicopathological parameters were also assessed. MVD and p53 status were analyzed immunohistoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
1
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 34 publications
4
22
1
2
Order By: Relevance
“…The mean value of MVD found by us was within the range of values reported by other authors (discussed in [23,24]). We confirmed no correlation between LVD (or DPV) and MVD [25].…”
Section: Discussionsupporting
confidence: 92%
“…The mean value of MVD found by us was within the range of values reported by other authors (discussed in [23,24]). We confirmed no correlation between LVD (or DPV) and MVD [25].…”
Section: Discussionsupporting
confidence: 92%
“…We have found a statistically significant relationship between increasing tumor size and mVD (p=0.001). There are consistent studies (19-21) with our results in the literature as well as some studies (16,22) found no significant relationship between mVD and tumor size and some studies found an inverse correlation between them (23).…”
Section: Discussionsupporting
confidence: 91%
“…In the literature, some studies have reported that there is no relationship between mVD and prognostic parameters such as patient's age (25,27), histological grade (28), lymphovascular invasion (9), estrogen and progesterone receptor status (27), HEr2/neu overexpression (27). On the other hand, there are also some other studies that found a significant relationship between high mVD and patient's age (29), high histologic grade (16,25,27), presence of lymphovascular invasion (30), estrogen (16,22) and progesterone receptor negativity (22) and HEr2/neu overexpression (31).…”
Section: Discussionmentioning
confidence: 96%
“…The prognostic value of MVD has remained controversial since its introduction twenty years ago: some initial studies have suggested that the MVD is a major independent prognostic factor for overall survival in invasive breast cancer (de Jong et al, 2000), but other studies have concluded that the MVD does not predict poor outcomes of invasive breast cancer (Kanjanapanjapol et al, 2007). Some recent research results have suggested that higher MVD is a favorable prognostic factor for early advanced breast cancer patients after adjuvant anthracycline-based chemotherapy (Biesaga et al, 2012). The authors of that study have speculated that differential distribution of MVD in tumors might be one of the reasons for different outcomes.…”
Section: Discussionmentioning
confidence: 99%